Efekt erlotinibu u pacientů se spinocelulárním karcinomem plic ve 2. a 3. linii protinádorové léčby - kazuistická sdělení - Šatánková, M; Brat, K; Tomíšková, M; Robešová, B; Skřičková, J (Klinicka onkologie, 2017)
BACKGROUND: Squamous cell carcinoma of the lung (SCC) represents cca 30-40% of new cases of non-small cell lung cancer (NSCLC) in the Czech Republic. The tyrosine kinase inhibitor erlotinib is indicated as a 1st line treatment for patients with locally advanced and metastatic disease and activating mutations in endothelial growth factor receptor (EGFR), or as a 2nd or 3rd line treatment in EGFR-negative NSCLC patients after chemotherapeutic failure. OBSERVATION: We present three case reports of patients with SCC treated with erlotinib as a 2nd or 3rd line of treatment. All patients were verified by histological analysis of tumor samples. EGFR mutation status was negative in one patient, while the other samples were not suitable for genetic screening. RESULTS: The therapeutic response to erlotinib lasted for 68, 40, and 13 months, resp. The patient with the longest therapeutic response (patient no. 1) is still continuing erlotinib treatment (as of December 2016). The overall survival of the two patients who died was 50 and 43 months, resp. One patient died of an unknown cause with no signs of progression of the disease on CT scans. The other patient died of terminal progression of the oncological disease. All three patients experienced major therapeutic benefit from erlotinib treatment as shown by the long periods of progression-free survival and prolonged overall survival. CONCLUSION: The three case reports demonstrate that erlotinib may be effective as a 2nd or 3rd line treatment in patients with SCC, especially in patients with limited alternative anticancer treatment options.Key words: non-small cell lung cancer - squamous cell carcinoma - erlotinib - treatment - tyrosine kinase inhibitor The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study. The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 5. 8. 2016Accepted: 14. 12. 2016.
Keywords: Erlotinib Hydrochloride; protinádorové látky; nádory plic; Salvage Therapy; Female; Aged; Antineoplastic Agents; spinocelulární karcinom; Carcinoma, Squamous Cell; Lung Neoplasms; Humans; ženské pohlaví; erlotinib; senioři; lidé; záchranná terapie